Biocompatible succinic acid-based polyesters for potential biomedical applications: fungal biofilm inhibition and mesenchymal stem cell growth1. Issue 104 (11th November 2015) - Jäger, E.; Donato, R. K.; Perchacz, M.; Jäger, A.; Surman, F.; Höcherl, A.; Konefał, R.; Donato, K. Z.; Venturini, C. G.; Bergamo, V. Z.; Schrekker, H. S.; Fuentefria, A. M.; et al.
<x xml:space="preserve">Abstract</x> Poly(alkene succinates) are promising materials for specialized medical devices and tissue engineering, presenting intrinsic properties, such as; fungal biofilm inhibition, biocompatibility and stem cells controlled growth promotion.